Comparative Analysis of the Effects of Annealing, Normalizing, and Hardening Heat Treatments on the Characteristics of ST60 Steel - Dewi 'Izzatus Tsamroh; Warkoyo (RING ME, 2026)
ST60 steel is widely used in manufacturing applications, including components of agricultural machinery such as shafts, transmission elements, and structural parts that require adequate strength and durability. Heat treatment is a commonly applied process to modify the microstructure and mechanical properties of ST60 steel according to specific engineering requirements. This study aims to comparatively analyze the effects of annealing, normalizing, and hardening heat treatments on the hardness and microstructural characteristics of ST60 steel. The experimental procedure involved heating ST60 steel specimens to the austenitizing temperature, followed by different cooling methods corresponding to each heat treatment process. The treated specimens were subsequently evaluated through Rockwell hardness testing and optical microscopy observations. The results showed that heat treatment significantly influenced the hardness and microstructure of ST60 steel. The highest average hardness was obtained from the hardening process, reaching 87.4 HRC, due to the formation of a predominantly martensitic microstructure during rapid cooling. The normalizing process produced an average hardness of 53.9 HRC and was characterized by the formation of fine pearlite, providing a balance between strength and toughness. Meanwhile, the annealing process yielded the lowest average hardness of 29.5 HRC, associated with the development of coarse pearlite, which enhanced ductility and machinability. Microstructural analysis confirmed a strong relationship between cooling rate, phase transformation, and hardness variation. These findings demonstrate that the selection of an appropriate heat treatment method is crucial for tailoring the properties of ST60 steel to meet the performance requirements of agricultural machinery and other industrial applications.